Comparative analysis of dentoalveolar arch morphometric parameters in case of arch shape variations - D. A. Domenyuk; E. G. Vedeshina; S. V. Dmitrienko; Zh. S. Orfanova (Кубанский научный медицинский вестник, 2015)
Scientific studies and clinical observations confirm that human dental arch forms reveal a great variety. There has been an analysis conducted aiming at detecting the interrelation between sagittal and transversal sizes of maxillary dental arches in 287 patients (both sexes; in their early adulthood, aged 21-35) with physiological occlusion of permanent teeth. Three types of maxillary dental arches were proposed: vestibular dental arch, alveolar lingual (palatal) arch, and dentoalveolar arch. There has been an interrelation established between the sagittal (the depth of the arch) and transversal (the width of the arch) sizes of the maxillary dental arches, and to evaluate the dental arch form it has been recommended to determine the arch index (the ratio between its depth and width). With the dental arch index of 0.74±0.03 the arch form was defined as mesognathic; the dentoalveolar arch and alveolar arch index then was 0.9±0.05. In case of a dental arch index below 0.7, the dentoalveolar arch and alveolar arch index being less than 0.85, the arch form was viewed as brachygnathic. The form was classified as dolichognathic in case the index went beyond 0.77 with the dentoalveolar arch and alveolar arch indices exceeding 0.95.